Chitosan suppresses the expression level of WRKY17 on red chili (Capsicum annuum) plant under drought stress - Muhammad Abdul Aziz; Rizkita Rachmi Esyanti; Karlia Meitha; Fenny Martha Dwivany; Hany Husnul Chotimah (Universitas Gadjah Mada, 2020)
Chili pepper plays a significant role in the global market. However, the production is often impeded by drought stress involving WRKY genes as the defense regulator. Chitosan is considered as a promising alternative fertilizer and defense elicitor. Hence, this study aimed to determine the role of chitosan in improving plant growth and survival of red chili pepper against drought stress. At the onset of the generative phase, chili plants were subjected to 1 mg mL‐1 chitosan, 50 percent drought, or chitosan‐drought treatment. Observations were made on several growth parameters, opened stomata, and WRKY gene expression. The results showed that chitosan‐drought treatment decreased plant growth and yielded significantly. The percentage of opened stomata was recorded at 0.56‐fold lower than control. It was followed by the decrease of the relative expression of WRKY17 and WRKY53 genes up to 0.56 and 0.72‐fold lower than control, respectively. Therefore, we suggested that the double treatment of chitosan‐drought might decrease plant growth performance but increase the defense system by suppressing the expression level of the WRKY17 gene. Interestingly, the drought treatment significantly increased WRKY17 expression level up to 7‐fold higher than control. Hence, it was suggested that WRKY17 has a specific role in response to drought stress.